2019
DOI: 10.1007/978-3-030-30611-3_17
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Career Trajectories of Cricket Players Using Gaussian Processes

Abstract: In the sport of cricket, variations in a player's batting ability can usually be measured on one of two scales. Short-term changes in ability that are observed during a single innings, and long-term changes that are witnessed between matches, over entire playing careers. To measure long-term variations, we derive a Bayesian parametric model that uses a Gaussian process to measure and predict how the batting abilities of international cricketers fluctuate between innings. The model is fitted using nested sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The derivation of the model likelihood for a single innings follows the method detailed in Brewer (2008) and Stevenson and Brewer (2017, 2018). If X ∈ {0, 1, 2, 3,…} is the number of runs a batsman scores in a particular innings, we define a hazard function , H ( x ) ∈ [0,1], as the probability a batsman gets out on score x , that is, H ( x ) = P ( X = x | X ≥ x ).…”
Section: Model Specificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The derivation of the model likelihood for a single innings follows the method detailed in Brewer (2008) and Stevenson and Brewer (2017, 2018). If X ∈ {0, 1, 2, 3,…} is the number of runs a batsman scores in a particular innings, we define a hazard function , H ( x ) ∈ [0,1], as the probability a batsman gets out on score x , that is, H ( x ) = P ( X = x | X ≥ x ).…”
Section: Model Specificationmentioning
confidence: 99%
“…A number of covariance functions are available to choose from, depending on how much we wish to allow player ability to fluctuate between innings. A common choice is the squared exponential covariance function, which was the choice of covariance function in Stevenson and Brewer (2018). However, we have since determined that the squared exponential function does not allow for enough short‐term variation in ability between innings since it implies smooth functions with high prior probability.…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…With thisa new model of batting average was developed which suggested that Geometric distributions come into play and in which number of not outs also play a vital role.Inthe context of geometric distributions, batting consistency is also which mattered a lot while evaluating player performance (12) . Moreover, to measure batsmen performance and consistency a new gaussian model was developed, which measured fluctuations between the innings played by a batsman in different matches (13) . On the same lines, gaussian model which takes cricket statistics into consideration, was developed which was used to assess batsmen performance in the longest form of cricket i.e.…”
Section: Annals Of Tropicalmentioning
confidence: 99%
“…In an attempt to rank all-rounders in test cricket, Tan and Ramachandran (2010) utilized both batting and bowling statistics to devise a mathematical formula. In another study, Stevenson and Brewer (2019) derived a Bayesian parametric model to predict how international cricketers' abilities change between innings in a game. Furthermore, Christie (2012) researched physical requirements of fast bowlers and stated the necessity of physiological demands to evaluate bowlers' performances.…”
Section: Introductionmentioning
confidence: 99%